Morphological and Comparative Transcriptome Analysis of Three Species of Five-Needle Pines: Insights Into Phenotypic Evolution and Phylogeny - Li, Xiang; Cai, Kewei; Zhao, Qiushuang; Li, Hanxi; Wang, Xuelai; Tigabu, Mulualem; Sederoff, Ronald; Ma, Wenjun; Zhao, Xiyang (Frontiers in Plant Science, 2022)
Pinus koraiensis, P. sibirica and P. pumila are the major five-needle pines in northeast China, with substantial economic and ecological value. The phenotypic variation, environmental adaptability and evolutionary relationships of these three five-needle pines remain largely undecided. It is therefore important to learn their genetic differentiation and evolutionary history. To obtain more genetic information, the needle transcriptomes of the three five-needle pines were sequenced and assembled. To explore the relationship of sequence information and adaptation to a high mountain environment, measurements were obtained describing needle morphology and climate for six natural populations. Four needle parameters were measured, needle length, needle width, needle thickness and fascicle width. Data for 19 bioclimatic variables describe the patterns and intensity of temperature and precipitation at their locations. Geographic coordinates of altitude, latitude and longitude were also obtained. The needle morphological data was combined with transcriptome information, location and climate data, for a comparative analysis of the three five-needle pines. We found significant differences for needle traits among the populations of the three five-needle pine species. Temperature, precipitation and altitude are the main factors limiting the natural distribution of these pines. Transcriptome analysis showed that the phenotypic variation and environmental adaptation of the needles of P. koraiensis, P. sibirica and P. pumila were related to photosynthesis, respiration, and metabolites. Analysis of orthologs from 11 Pinus species indicated a closer genetic relationship between P. koraiensis and P. sibirica compared to P. pumila. Our study lays a foundation for genetic improvement of these five-needle pines and provides insights into the adaptation and evolution of Pinus species.